Violence against Canadian Women - Maclean Heather; Cohen Marsha M (BMC, 2004)
Abstract Health Issue Exposure to violence as children or as adults places a woman at higher risk of poor health outcomes, both physical and psychological. Abused women use more health care services and have poorer social functioning than non-abused women. Knowledge of the prevalence of violence against women, and of which women are at risk, should assist in the planning of services for abuse prevention and treatment of the health consequences of abuse. Key Findings The highest rates of any partner violence were in Alberta (25.5%) and British Columbia (23%). The lowest rates were in Ontario (18.8%). Women aged 15-24 had the highest rates in all regions in Canada, compared with older women. Aboriginal women in Manitoba/Saskatchewan and Alberta had higher rates of violence (57.2% and 56.6% respectively) than non-Aboriginal women (20.6%). Lower rates of partner-related violence were reported among women not born in Canada (18.4%) than among Canadian-born women (21.7%). Visible minority women reported lower rates of lifetime sexual assault (5.7%) than non-visible minority women (12.3%). Perceptions of violence may vary by ethnicity. Data Gaps and Recommendations More information is required concerning the prevalence of violence among Aboriginal women, immigrant and refugee women, women with disabilities, lesbian women and pregnant women. Future national population-based surveys need better questions on the health consequences of violence and related resource utilization. Further research is needed to identify the health care system's role in prevention, management and rehabilitation as they relate to violence against women. Future programs and policies must be based on valid, reliable and comprehensive empirical data.